2003
DOI: 10.1093/chemse/28.6.545
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Wasps Learn and Report Diverse Chemicals with Unique Conditionable Behaviors

Abstract: Parasitoids exploit numerous chemical cues to locate hosts and food. Whether they detect and learn chemicals foreign to their natural history has not been explored. We show that the parasitoid Microplitis croceipes can associate, with food or hosts, widely different chemicals outside their natural foraging encounters. When learned chemicals are subsequently detected, this parasitoid manifests distinct behaviors characteristic with expectations of food or host, commensurate with prior training. This flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…We have successfully conditioned M. croceipes to learn and discriminate bouquets of fungal odors as previous studies have successfully shown this wasp's ability to learn and recognize single chemicals associated with food and/or host (Tertuliano et al 2004;Olson et al 2003;. These results are in accordance with other studies that demonstrate a wide range of learning ability in insects (Daly & Smith 2000;Gunningham et al 1998).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We have successfully conditioned M. croceipes to learn and discriminate bouquets of fungal odors as previous studies have successfully shown this wasp's ability to learn and recognize single chemicals associated with food and/or host (Tertuliano et al 2004;Olson et al 2003;. These results are in accordance with other studies that demonstrate a wide range of learning ability in insects (Daly & Smith 2000;Gunningham et al 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have shown that Microplitis croceipes Cresson (Hymenoptera: braconidae), a larval parasitoid of Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) and Heliothis virescens (F) (Lepidoptera: Noctuidae) (Lewis 1970) has the ability to learn novel chemical odors (Tertuliano et al 2004;Olson et al 2003;Wäckers et al 2002;Takasu & Lewis 1993;1996). Additionally, food and host-associated behaviors, such as area-restricted searching (food-associated behavior) and coiling (host-associated behavior whereby female wasps rise on their hind legs with a characteristic bending of their antennae) (Olson et al 2003) exhibited by conditioned wasps are distinctly observable and suitable for use as a diagnostic method for detecting conditioning chemicals (Olson et al 2003;Wäckers et al 2002). This wasp has also exhibited specific yet respectively different behaviors for the same chemical odor when associated with food (food seeking) versus with host (coiling) (Olson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquitoes were conditioned to a target odor in association with a sugar-or blood-meal using methods adapted from Olson et al (2003). Mosquitoes were starved for 24 h before their use in an experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Visual associative learning in honey bees Apis mellifera Linnaeus (Hymenoptera: Apidae) also has been documented (e.g., Srinivasan 1994;Zhang et al 1996;Horridge 1997). Behaviors linked to the expectation of a target resource (food or host) through associative learning for M. croceipes are resource specific and are not exhibited in association with other resources such as hosts (Olson et al 2003). Therefore, these behaviors are an appropriate means for measuring the plasticity of their learning ability in association with a specific resource.…”
mentioning
confidence: 99%